Perdagangan budak di pulau NIAS 1820-1860 = Slave trade in NIAS Island 1820-1860 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The title of the thesis is the Slave Trade in Nias Island, in 1820-1860. The topic of the history of slave trade has not been extensively studied. The background of choosing Nias Island as the object of the research is derived from data which shows that Nias Island supplied large numbers of slaves among other areas in western Nusantara at the time. The research purpose is to reconstruct the history of the slave trade in Nias Island during the period after Thomas Stamford Raffles, the British Governor of Bengkulu sent a commision who, together with local native in Nias authorities, made an agreement to prohibit the slave-trade activities there. The research applies historical method. Based on the method, this research analyzes a great number of historical sources, either the documents or other written sources which discuss the slave trade in Nias Island. The data used in this research are taken from Indonesian National Archives and various libraries. To focus the analysis, the research also uses some concepts from some social sciences. The results of the research reveal the facts that the prohibition of the slave-trade in 1820 did not influence the slave trade in that island. For the next 40 years, the data shows that the slave trade still existed exactly as it had previously. This situation was fostered by two important things. First, the internal social-cultural condition of Nias society still kept the existence of the institution of slavery. Thus, there was always the stock commodity of men ready for trading. Second, from external necessities of human service to work in some areas especially in Sumatra, caused a continuing demand for this kind of human commodity. Key words: Nias Island slavery slave trade